Antibacterial Activity Of Tetrapleura Tetraptera Taub. Pod Extracts - UCHECHI .N. EKWENYE,; CHIGOZIE.F. OKORIE, (International Journal of Pharma and Bio Sciences, 2010)
Phytochemical composition and antibacterial activity of ethanolic and water extract of Tetrapleura tetraptera were studied. Four known human bacterial pathogens were used. They were Escherichia coli ,Staphylococcus aureus, Salmonella typhi and Pseudomonas aeruginosa.The test plant yielded 2.322% of extract with water and 3.180% of extract with ethanol. Also, phytochemical composition revealed the presence of tannin,0.36%:saponin,0.54%;flavonoid,0.84%;alkaloid,1.28%:phenol,0.42% and 9.86mg/kg of hydrocyanic acid (HCN).Both water and ethanol extracts showed strong antibacterial activity. The water extract gave inhibition zone of diameters 14.1mm,11.0mm,12.9mm and 20.4mm with Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella typhi respectively,while ethanol extract gave 20.1mm,26.4mm,24.8mm and 14.0mm of the same test organisms. It was recorded that ethanolic extracts were more potent against the test organisms than the water extract.The established antibacterial activities were attributed to the presence of phytochemical and the continuous use of the test plant was highly recommended.